2016
DOI: 10.1117/1.jatis.2.2.025003
|View full text |Cite
|
Sign up to set email alerts
|

SAXO: the extreme adaptive optics system of SPHERE (I) system overview and global laboratory performance

Abstract: International audienceThe direct imaging of exoplanet is a leading field of today’s astronomy. The photons coming from the planet carry precious information on the chemical composition of its atmosphere. The second-generation instrument, Spectro-Polarimetric High contrast Exoplanet Research (SPHERE), dedicated to detection, photometry and spectral characterization of Jovian-like planets, is now in operation on the European very large telescope. This instrument relies on an extreme adaptive optics (XAO) system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…This was used to produce a 2D attenuation profile of the coronagraph for an extended, incoherent source. Monochromatic Fourier modeling of the threeplane APLC coronagraph was also performed, using the APO1 SPHERE amplitude apodiser, ACL2 (185 mas diameter) focalplane mask and NIR Lyot stop including dead actuator masks (Guerri et al 2011, Sauvage et al 2016. This model confirmed that the observed Ceres attenuation profile is nearly diffractionlimited and azimuthally symmetric.…”
Section: Inner and Outer Radiusmentioning
confidence: 62%
“…This was used to produce a 2D attenuation profile of the coronagraph for an extended, incoherent source. Monochromatic Fourier modeling of the threeplane APLC coronagraph was also performed, using the APO1 SPHERE amplitude apodiser, ACL2 (185 mas diameter) focalplane mask and NIR Lyot stop including dead actuator masks (Guerri et al 2011, Sauvage et al 2016. This model confirmed that the observed Ceres attenuation profile is nearly diffractionlimited and azimuthally symmetric.…”
Section: Inner and Outer Radiusmentioning
confidence: 62%
“…The star HR 4796 A was observed on the night of 24 May, 2016, with the Spectro-Polarimetric High-contrast Exoplanet REsearch instrument (SPHERE Beuzit et al 2019). SPHERE is a high-contrast imager fed by an extreme adaptive optics (AO) system (Sauvage et al 2016b) to correct for the atmospheric turbulence and static aberrations. These observations were part of the Guaranteed Time Observations of the SPHERE consortium 1 and made use of the visible subsystem Zurich IMaging POLarimeter (ZIMPOL, Schmid et al 2018) to observe the star in linear polarized light.…”
Section: Instrumental Setupmentioning
confidence: 99%
“…It is used to measure and correct any incoming wavefront perturbation (rapidly varying turbulence or quasi-static instrumental speckles) to ensure a high image quality. The system is fully specified in Fusco et al (2006) and all the laboratory validations and performance are detailed in Sauvage et al (2016b) and Petit et al (2012). The results presented in this section correspond to the SAXO configuration validated during SPHERE commissioning and science verification periods.…”
Section: High-level Technical Requirements and Designmentioning
confidence: 99%